Enhancing the decolorization of methylene blue using a low-cost super-absorbent aided by response surface methodology - Abdullah, N. H.; Mohamed, M.; Mohd Shohaimi, N. A.; Lazim, A. M.; Abdul Halim, A. Z.; Mohd Shukri, N.; Abdul Razab, M. K. A. (MDPI AG, 2021)
The presence of organic dyes from industrial wastewater can cause pollution and exacerbate environmental problems; therefore, in the present work, activated carbon was synthesized from locally available oil palm trunk (OPT) biomass as a low-cost adsorbent to remove synthetic dye from aqueous media. The physical properties of the synthesized oil palm trunk activated carbon (OPTAC) were analyzed by SEM, FTIR-ATR, and XRD. The concurrent effects of the process variables (adsorbent dosage (g), methylene blue (MB) concentration (mg/L), and contact time (h)) on the MB removal percentage from aqueous solution were studied using a three-factor three-level Box–Behnken design (BBD) of response surface methodology (RSM), followed by the optimization of MB adsorption using OPTAC as the adsorbent. Based on the results of the analysis of variance (ANOVA) for the three parameters considered, adsorbent dosage (X1) is the most crucial parameter, with an F-value of 1857.43, followed by MB concentration (X2) and contact time (X3) with the F-values of 95.60 and 29.48, respectively. Furthermore, the highest MB removal efficiency of 97.9% was achieved at the optimum X1, X2, and X3 of 1.5 g, 200 mg/L, and 2 h, respectively